The Impact of Information on Job Choices and Turnover - Caldwell, David F.; O’Reilly, Charles A. (Academy of Management Journal, 1985)
In this article the authors discuss research they conducted on the relationship between employee turnover and their access to accurate information about their job. The authors hypothesized that individuals who received accurate information about their job would have lower turnover levels than individuals who had inaccurate information, that individuals who used inaccurate information sources would have higher turnover rates than individuals who used more informative sources and that individuals who believed they received accurate information would be positively correlated to the extent to which they used personal or formal sources for obtaining job information. The authors discuss that it has been show that good decision making is positively correlated with access to accurate information.